Diabetic neuropathic cachexia: report of a recurrent case. Issue 6 (1st June 1998) - Jackson, Carlayne E; Barohn, Richard J
Abstract : Diabetic neuropathic cachexia is an uncommon peripheral neuropathy associated with diabetes mellitus and characterised by profound weight loss and painful dysaesthesias over the limbs and trunk. The pathophysiological basis of this disorder remains unknown and there have been no published cases of recurrent episodes. A hispanic man who experienced two episodes of diabetic neuropathic cachexia over a seven year period is described.